"My day-to-day person wasn't there; it was like another me": A qualitative study of spiritual experiences during peak performance in ballet dance. Issue 1 (March 2016) - Flower, Lynda
Highlights: Interpretation of spiritual experiences in ballet peak performance. Lived experience of spiritual experiences through ballet were 'extraordinary'. Spiritual experiences continued into other dance related activities (e.g. teaching and writing). Abstract: This study reviews spiritual lived experiences (secular and religious) reported during peak performance in the performing art of ballet. This review is located in academic discussions of mystical and spiritual experiences in the Western cultural tradition. A small sample of seven selected former professional ballet dancers was interviewed using qualitative research with an interpretative phenomenological analysis (IPA) approach. The findings made evident four major themes: the peak performance lived experience was 'extraordinary'; the experience continued in a 'post-performance high'; the experience was described as spiritual; and an overall love for ballet. These findings not only confirm previous research but also provide in-depth insights into the spiritual aspect of peak performance in a way other studies in contemporary times do not. A summary table of the findings is included.